Effect of Cropping on Aggregation and some other Properties of Acidic Soils of Kanke (Ranchi) - Mahant; Singh, R.A. (Journal of Soil and Water Conservation, 2022)
As soon as cultivation begins, many changes are brought about in the physical, chemical, and biological properties of a soil. The magnitude and the character of the changes taking place depend largely on the crop and the soil management practices employed in its production. The farmers of Chotanagpur, the hilly tract of Bihar, are growing crops mostly in monsoon season continuously in the same field year after year. Very little crop rotation is followed due to lack or excess of soil moisture and deficiency of some of the nutrient elements. It is, therefore, necessary to study the effects of continuous cropping on the properties of Chotanagpur soils. Very little such work has been done on these soils. With this in view, the study of the effects of continuous cropping on the physical properties of Kanke soils was undertaken.